Cold water immersion after a soccer match: Does the placebo effect occur? - Nasser, N.; Zorgati, H.; Chtourou, H.; Guimard, A. (Frontiers in Physiology, 2023)
Although cold water immersion (CWI) is one of the most widely used post-exercise strategies to accelerate recovery processes, the benefits of CWI may be associated with placebo effects. This study aimed to compare the effects of CWI and placebo interventions on time course of recovery after the Loughborough Intermittent Shuttle Test (LIST). In a randomized, counterbalanced, crossover study, twelve semi-professional soccer players (age 21.1 ± 2.2 years, body mass 72.4 ± 5.9 kg, height 174.9 ± 4.6 cm, V? O2max 56.1 ± 2.3 mL/min/kg) completed the LIST followed by CWI (15 min at 11°C), placebo (recovery Pla beverage), and passive recovery (Rest) over three different weeks. Creatine kinase (CK), C-reactive protein (CRP), uric acid (UA), delayed onset muscle soreness (DOMS), squat jump (SJ), countermovement jump (CMJ), 10-m sprint (10 mS), 20-m sprint (20 mS) and repeated sprint ability (RSA) were assessed at baseline and 24 and 48 h after the LIST. Compared to baseline, CK concentration was higher at 24 h in all conditions (p < 0.01), while CRP was higher at 24 h only in CWI and Rest conditions (p < 0.01). UA was higher for Rest condition at 24 and 48 h compared to Pla and CWI conditions (p < 0.001). DOMS score was higher for Rest condition at 24 h compared to CWI and Pla conditions (p = 0.001), and only to Pla condition at 48 h (p = 0.017). SJ and CMJ performances decreased significantly after the LIST in Rest condition (24 h: -7.24%, p = 0.001 and -5.45%, p = 0.003 respectively; 48 h: -9.19%, p < 0.001 and -5.70% p = 0.002 respectively) but not in CWI and Pla conditions. 10 mS and RSA performance were lower for Pla at 24 h compared to CWI and Rest conditions (p < 0.05), while no significant change was observed for 20 mS time. These data suggests that CWI and Pla intervention were more effective than the Rest conditions in recovery kinetics of muscle damage markers and physical performance. Furthermore, the effectiveness of CWI would be explained, at least in part, by the placebo effect.